Parental treatment Styles and their relationship with social anxiety among middle school students in Jeddah - Al- Qahtani, Manie Murei’ Abu Dabil (Journal of Educational and Psychological Sciences, 2022)
The aim of this research is to identify the parental treatment styles and their relationship with social anxiety among intermediate school students in Jeddah, by identifying each of the social anxiety levels among intermediate school students in Jeddah, and most common the parental treatment styles among the parents of the intermediate school students in Jeddah. The research adopted the descriptive, relational approach, (The study population consisted of middle school students (third intermediate school) and applied to a sample of (109) students. Parental treatment styles scale for Al- Nefa’i (1998) and social anxiety scale for Al- Ammari (2016) were applied to sample. The research found that the most common parenting treatment style by the father and mother were: the guideline indicative style followed by the confirm power or punitive style while the love withdrawal style came in the last place, and that the social anxiety levels in general among intermediate school students in Jeddah is low, as well it found a positive significant relationship between (confirm power or punitive style) and the love withdrawal style (emotional deprivation)) by the fathers and social anxiety among middle school students in Jeddah. Also there is a positive significant relationship between (confirm power or punitive style) and the love withdrawal style (emotional deprivation)) by the mothers and social anxiety among intermediate school students in Jeddah. Based on the findings of the research, the researcher recommended that parents should make more opportunities for social interaction, communication, and social relations, and to encourage their children to express feelings of acceptance, and to encourage them to have feelings of independence, self- reliance, and freedom of expression whenever they can.
Keywords: Treatment methods; parenting methods; social anxiety; Intermediate school students